Introduction to the Special Issue: Music and Subalternity through the Popular and Periphery, or How to Use Popular Music for Several Debates at the same Time. (14th October 2017) - Alabarces, Pablo; Trotta, Felipe
Abstract : It is not difficult to see the enormous clout of aesthetic production associated with the "popular", which increasingly enters the imaginaries shared extensively in several Latin American countries (and beyond). They are cultural practices that circulate on television channels, the internet, in parties and concerts of various sizes, implementing the idea of "popular" in some form. In this whirlwind of sights, sounds and stereotypes around the "popular world", music is certainly one of the artefacts that most disseminates the "aesthetics of the periphery". Artists such as Michel Teló, Aviões do Forró, Mr. Catra, Damas Grátis, Pibes Chorros, Don Omar and Calle 13 are linked to ways of saying, acting and thinking of the periphery (in its various social and territorial meanings), and circulate around the industry of world culture implementing sounds and thoughts that frequently collide with intellectualized aspects of life and discourse. In Latin America, some musical practices highlight heated debates about ethics and aesthetics, dealing with thoughts on the geographical and social hierarchy of our societies. This special issue, including its introduction, intends to present some of these discussions, focusing on three key categories in Latin American debates: popular, subalternity and periphery (in the complex meaning of social and territorial separation, but also in production from beyond the centre of the Western world: in the music scene, and also in academia).